(3efGbH CHj SYjO GdeUQi GdMSfi Gdecfi HKhHIs
(3ChdgG (B:s
(3gPG efGbH GdTjN G dMSf SjOi CHj SYjO GdeUQi , Gdecfi H KhHI , faYfG Gddg Hg s
(3BNQgG (B:s
(3Hbi ef HYOge GdTjN YHO GdLdjd CjGe jHci Gddjd hGdfgGQ MJi CJGg Gdjbjf aeGJ QMeI Gddg Ydjg GfJgJ s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B2 - (3bSe (B5 - (3U (B190 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdNRGfI GdYGeI (B_ (3GdQHGW (B(1485(3O(B) s
Keywords: (3GdJGQjNs